Module of Leadership Excellence Programme for Chief Librarians & Deputy Chief Librarians of Higher Education Institution - Zaharah Abd Samad,; Aryanti Ahmad,; Salawati Ahmad, (2023)
The ExceLib module is an initiative by the Ministry to strengthen leadership competencies among senior academic library officers through seven core leadership modules. Conducted online from August 2021 to January 2022, the programme engaged 40 participants from 20 public university libraries. With the support of AKEPT, expert speakers, and facilitators, the programme serves as a key reference to enhance leadership capabilities, management styles, and governance practices among Chief Librarians and Deputy Chief Librarians within academic library institutions.